Anthracene‐containing conjugated polymer showing four optical transitions upon doping: A spectroscopic study. Issue 4 (28th November 2013) - Gasiorowski, Jacek; Boudiba, Sameh; Hingerl, Kurt; Ulbricht, Christoph; Fattori, Valeria; Tinti, Francesca; Camaioni, Nadia; Menon, Reghu; Schlager, Stefanie; Boudida, Louiza; Sariciftci, Niyazi Serdar; Egbe, Daniel Ayuk Mbi
ABSTRACT An anthracene‐containing poly(arylene‐ethynylene)‐alt‐poly(arylene‐vinylene) (PAE‐PAV) of general constitutional unit (PhCCAnthrCCPhCHCHAnthrCHCH)n bearing two 2‐ethylhexyloxy solubilizing side chains on each phenylene (Ph) unit has been synthesized and characterized. The basic electrochemical characterization was done, showing the existence of two non‐reversible oxidation and one reversible reduction peaks. The optical properties, the real and imaginary part of the dielectric function, were probed using spectroscopic ellipsometry (SE). The vibrational structure of the undoped/doped polymer was investigated using Fourier transformed infrared spectroscopy. A strong change in the polaronic absorption was observed during the doping, which after modeling revealed the existence of two separated transitions. The optical changes upon doping were additionally recorded using the SE technique. Similar to the results from FT‐IR spectroscopy, two new in‐the‐gap absorptions were found. Moreover, the electrical conductivity as well as the mobility of positive carriers were measured. In the undoped state, the conductivity of the polymer was found to be below the detection limit (<μS cm−1), after doping the conductivity increased to 0.69 S cm−1. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 338–346